Policy and practice targeting the labour market integration of non-EU nationals in Ireland - Samantha Arnold; Emma Quinn; Sarah Groarke; Frances McGinnity; Christina Durst (The Economic and Social Research Institute (ESRI), 2019)
Increases in immigration inflows to both the European Union (EU) and Ireland between 2014 and 2016 have resulted in an increased focus on integration policies, outcomes and measures, including in the area of labour market integration. Ireland, like the majority of EU Member States, pursues a policy of mainstreaming service provision in the area of integration, with targeted initiatives to meet specific needs. This study first considers labour migration policy, which manages and shapes overall access of non-European Economic Area (EEA) nationals to the Irish labour market. Under the employment permits system administered by the Department of Business, Enterprise and Innovation (DBEI), non-EEA nationals may apply to access the Irish labour market. The report also looks at specific policies and measures which aim to improve labour market integration for non-EU nationals living in Ireland. The focus is on labour integration measures for regularly staying non-EU nationals with a right to work. Measures specifically targeting non-EEA students, graduates, asylum seekers and beneficiaries of international protection are beyond the study scope. The effect of general labour market and social policy provision in Ireland on labour market integration is also outside the scope. Examples of public and private sector practices are discussed together with examples of community sector practices that receive public funds.
Keywords: 330